Is the R&D Behaviour of Fast Growing SMEs Different? Evidence from CIS III Data for 16 Countries - Werner Hölzl (Austrian Institute of Economic Research (WIFO), 2008)
This paper studies the R&D behaviour of fast growing SMEs using CIS III data for 16 countries. We group the countries into three groups that roughly have the same position in technological development. The first finding is that R&D is more important to high growth SMEs in countries that are closer to the technological frontier. The second finding is that high growth SMEs are more innovative than non-high-growth SMEs only for countries close to the technological frontier. This suggests that gazelles derive much of their drive from the exploitation of comparative advantages. From a policy perspective this suggests that there are important limits to centralise policies that aim at fostering high growth SMEs.
Keywords: 330; R&D; high growth firms; Europe; CIS; Industrieforschung; Unternehmenswachstum; Technische Effizienz; KMU; Europa